Biological factors and mannerisms as predictors for science achievement - Diego, Artemio A. (Animo Repository, 1990)
Using three hundred seventy-eight (378) third year students from ten selected schools in region I, this study is conducted with the main purpose of determining biological factors and mannerisms that could be correlated and predictive of science achievement in biology during the school year 1989-1990. The following factors were considered: handedness (X1), birth order (X2), tongue rolling (X3), type of ear lobe (X4), hand clasping (X5), arm folding (X6), leg crossing (X7), maternal age (X8), paternal age (X9), and motor coordination (X10). The results indicated that there was significant relationship between science achievement in biology and handedness and motor coordination. It was also found out that there was no significant relationship between science achievement in biology and birth order, tongue rolling, type of ear lobe, hand clasping, arm folding, leg crossing, maternal age and paternal age. Of the seven (7) biological factors and three (3) minor body mannerisms studied, only handedness and motor coordination were found to be good predictors of science achievement in biology.The study may have implications on cognitive development. Better science achievement in biology correlates high with motor coordination which implies that a proper environment is therefore just an important as the heritable traits in the development of the child. The study suggests further that environment has a marked influence on the rate of motor development, so various appropriate approaches or techniques like discovery, inquiry and individualized or group-paced instruction which emphasize manipulative activities may be implemented to enhance full development of motor skills. Science teachers especially should create a rich and varied environment in which children experience considerable motor skills development and given ample opportunity to learn cognitive skills. It implies further that parents should not be over protective of their children so as not to hamper the motor development of their children.